Factors that influence the use of the virtual library among students at a university in northeastern Mexico - Infante Alcántara, Lizbeth; Estrada Domínguez, Jesús Eduardo; Suárez Escalona, Rubén (Revista General de Información y Documentación, 2022)
Due to the quarantine of Covid 19, libraries have had to adapt to the virtual modality. For this reason, the present research aims to identify the factors that motivate students in the engineering area, at Universidad Autonoma de Nuevo Leon, in Mexico, to use the virtual library. A measurement instrument with 26 questions on a Likert scale was used, which meets the reliability and validity characteristics. The instrument was applied to a stratified sample of 386 students. Statistical analysis was performed using SPSS software, developing a multiple linear regression model. The results show that the variables: information available in the virtual library, the information skills of the librarian, the influence of the teacher, awareness of the value of information and reading habits directly influence the use of the virtual library. The resulting model provides valuable information on those critical factors that must be taken into account to strengthen the use of virtual libraries in universities by students. Likewise, it is recommended for future research to re-analyze the teacher’s influence factor in postpandemic times, hoping to find a different finding.